2015
DOI: 10.1016/j.psep.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Explosion behavior of n-alkane/nitrous oxide mixtures

Abstract: Explosion limitExplosion pressure Burgess-Wheeler law Gas explosion Deflagration index a b s t r a c tThe explosion properties of alkane/nitrous oxide mixtures were investigated and were compared with those of the corresponding alkane/oxygen and alkane/air mixtures. The explosion properties were characterized by three parameters: the explosion limit, explosion pressure, and deflagration index. For the same alkane, the order of the lower explosion limits (LELs) of the mixtures was found to be alkane/oxygen ≈ al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…As seen in Figs. 6 and (Koshiba et al, 2015), together with their flammability limits reported in the literature (Shebeko et al, 2013, Pfahl et al, 2000. .0 vol% and 2.0 vol% of LFL for a CH 4 -N 2 O mixture, respectively.…”
Section: Upper Flammability Limit and The Applicability Of Le Chatelimentioning
confidence: 79%
See 1 more Smart Citation
“…As seen in Figs. 6 and (Koshiba et al, 2015), together with their flammability limits reported in the literature (Shebeko et al, 2013, Pfahl et al, 2000. .0 vol% and 2.0 vol% of LFL for a CH 4 -N 2 O mixture, respectively.…”
Section: Upper Flammability Limit and The Applicability Of Le Chatelimentioning
confidence: 79%
“…Fig. 1 illustrates the experimental apparatus, which is identical to that used for a previous study (Koshiba et al, 2015). The closed, cylindrical stainless-steel vessel with a diameter of 100 mm and a height of 120 mm includes a fan for stirring, two tungsten electrodes ( 1.0 mm) for ignition, and two pressure transducers.…”
Section: Chemicals and Gasesmentioning
confidence: 99%
“…2 Therefore, the knowledge about explosion characteristics of syngas is essential to both the optimization design on syngas-fuelled applications and the safety protection strategies on storage and delivery of syngas. 9 However, the research works about explosion characteristics of syngas are very scarce in current literatures, and the reported information about explosion parameters are relative limited. 9 However, the research works about explosion characteristics of syngas are very scarce in current literatures, and the reported information about explosion parameters are relative limited.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit the fundamental research works about explosion characteristics have been excessively experimentally performed in the past decade, most of those works were conducted on hydrocarbon fuels, such as n-pentane, 3 propylene, 4 methane, 5 methyl ether, 6 nitromethane, 7 ethylene, 8 and n-alkane. 9 However, the research works about explosion characteristics of syngas are very scarce in current literatures, and the reported information about explosion parameters are relative limited. Such lacks are mainly attributed to 2 reasons: (a) compared to hydrocarbon fuels, the value of syngas in utilization abstracts attentions latter; and (b) different to those fuels have specific components, syngas has varieties in the detailed components for different sources and/ or different synthesis technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, some scholars contributed into the research about explosion characteristics of blended fuels, including blended fuels of pentane, hexane, and benzene [4], blended fuels of methane and carbon dioxide [5], blended fuels of liquefied petroleum gas [6], blended fuels of hydrogen and nitrogen oxides [7], the blended fuels of hydrogen and dust [8], the blended fuels of natural gas, argon, and nitrogen gas [9], blended fuels of n-alkane and nitrous oxide [10], blended fuels of butanol and octane [11], hydrogen/carbon monoxide blended fuels [12], blended fuels of hydrogen and methane [13]. As could 2 of 15 be seen, the works on the explosion characteristics of hydrogen/methane-blended fuels are relative new and scarce in the current literature.…”
Section: Introductionmentioning
confidence: 99%